APPLICATION OF THE INDEPENDENT CURRICULUM IN THE DEVELOPMENT OF ISLAMIC RELIGIOUS EDUCATION LEARNING ACTIVITIES IN MUHAMMADIYAH PRIVATE HIGH SCHOOL 02 MEDAN - Asmila, Winda; Kamil, Kamil (STIT Pringsewu, 2024)
The Merdeka Curriculuml isl anl educationall initiativel thatl emphasizesl independencel inl learning.l Thisl studyl usedl qualitativel descriptivel method.l Thel Merdekal Curriculuml makesl itl easyl tol simplifyl thel materiall froml beforel tol bel shortl andl easierl andl adaptedl tol thel needsl ofl studentsl inl everydayl life.l Teachersl playl anl importantl rolel inl thel teachingl andl learningl processl ofl developingl anl understandingl ofl religiousl andl morall values.l Inl addition,l itl wasl foundl thatl the application of the Merdeka Curriculum in the subject of Islamic Religious Education provides opportunities for students to be more in-depth in understanding Islam and develop strong moral character. This process also helps students develop better critical thinking skills, creativity, and communication skills. This research provides important insights about the implementation of the Merdeka Curriculum in Islamic Religious Education subjects at SMA Muhammadiyah 02 Medan, and can be an evaluation to develop the application of the Merdeka Curriculum and about how the Merdeka Curriculum can be applied well in Islamic religious education in other schools. The purpose of this study is to find out how the application of the Independent Curriculum in the Development of Islamic Religious Education Learning in Class XI of Muhammadiyah 02 Medan Private High School.